قضية في طباعة المصاحف القرآنية: الخلاف في علم العدد و تطبيقه في طباعة المصاحف القرآنية في العالم - Abd Muhaimin Ahmad; Sabri Mohamad; Haziyah Hussin (Department of Theology and Philosophy, Universiti Kebangsaan Malaysia, 2024)
Indexed by MyCite